Revitalizing Salaf Education: Development Trends Towards a Superior and Adaptive Pesantren - santoso, Budi; Robitulhaq, Robitulhaq; Irianti, Desi; Rofik, Ainur (Aksara Shofa, 2025)
This study aims to explain the revitalization of salaf education as a development trend towards superior and adaptive pesantren. This research emphasizes the importance of revitalizing salaf education to identify concrete steps that can be taken by pesantren in facing the challenges of the modern era. The research object focuses on Darussalam Islamic Boarding School. This research uses qualitative research methods with a case study approach. The research informants included the head of the boarding school and the head of the writing media extracurricular institution at Darussalam Islamic Boarding School. Data were collected through observation, interview, and documentation techniques. Data analysis was conducted using the Miles and Huberman model, which includes three main stages: data reduction, data presentation, and conclusion drawing. The results showed that the revitalization of salaf education as a development trend towards superior and adaptive pesantren includes several main aspects: (1) improvement of digital skills, (2) foreign language training, and (3) emphasis on religious moderation. The improvement of digital skills is very important considering that information and communication technology plays a crucial role in various aspects of modern life, including in the fields of education and employment.